KEPENTINGAN TIONGKOK DALAM PEMBENTUKAN SHANGHAI COOPERATION ORGANIZATION - Rolly Jean Marten; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to find Tiongkok interest in Shanghai Cooperation Organization, Shanghai Cooperation Organization is Central Asia Regional Organization with members is Tiongkok, Rusia, Kazakshtasn, krygyztan, Uzbekistan, and Tajikistan, Central Asia States is Country with rich natural resources. Tiongkok currently a country that has a very rapid economic development, but Tiongkok is also experiencing problems would need energy for it Indusrty`s, and therefore the Shangihai Cooperation Organization is the solution for Tiongkok, To Stregthen the relationship and Cooperation with the Countries Of Centarl Asia and Rusia for Secure energy demand. This research used kontrustivisme Perspective and apply regionalisme theory, how is Tiongkok use the Shanghai Cooperation Organization for his economy necessary,Tiongkok spreading effects of his Sosialisme Ideology in other Country With make a New Silk Road, more extensive than Before The final result of this research is Tiongkok interest in Shanghai Cooperation is the economic interests and Energy Secure in Central Asia, Tiongkok and Rusia have a mission to eliminate western influence in Central Asia,Tiongkok have a huge economic advantage in Central Asia as a market, have a Central Asia for Energy Secure in the Future, and have a good partner to make a multipolar world. With Shanghai Cooperation Tiongkok also simplify its relationship with Africa and Latin America for import them energy.Keyword : Shanghai Cooperation Organization, Energy Secure, Economic Interest, Sosialisme Ideology, and New Slik Road Plan